2017
DOI: 10.1038/s41598-017-15844-1
|View full text |Cite
|
Sign up to set email alerts
|

The WD40-domain containing protein CORO2B is specifically enriched in glomerular podocytes and regulates the ventral actin cytoskeleton

Abstract: Podocytes are highly specialized epithelial cells essentially required to establish and maintain the kidney filtration barrier. Due to their complex cellular architecture these cells rely on an elaborated cytoskeletal apparatus providing plasticity as well as adaptive adhesion properties to withstand significant physical filtration forces. However, our knowledge about podocyte specific components of the cytoskeletal machinery is still incomplete. Employing cross-analysis of various quantitative omics-data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Context dependent requirements are also reflected by a cell type specific composition of the cytoskeleton, as demonstrated by others and us (e.g. SYNPO, ARHGAP24 or CORO2B –[ 17 , 31 , 32 ]). Proteomic analysis for selectively or highly enriched expression of cytoskeletal proteins led to the identification of AIF1L in glomerular epithelial cells ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Context dependent requirements are also reflected by a cell type specific composition of the cytoskeleton, as demonstrated by others and us (e.g. SYNPO, ARHGAP24 or CORO2B –[ 17 , 31 , 32 ]). Proteomic analysis for selectively or highly enriched expression of cytoskeletal proteins led to the identification of AIF1L in glomerular epithelial cells ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 66%
“…Measurement of focal adhesions was performed as described previously [ 17 ]. In brief, human immortalized podocytes were cultured on collagen IV coated glass coverslips and immunofluorescence staining was performed for the focal adhesion component PAXILLIN.…”
Section: Methodsmentioning
confidence: 99%
“…As Coro2b was recently reported to localize to focal adhesions at the basal aspects of podocyte foot processes 9,10 , we analyzed in more detail the distribution of Coro2b in podocytes. We applied an optical clearing protocol to a mouse kidney expressing tdtomato in podocytes to perform high resolution imaging.…”
Section: Resultsmentioning
confidence: 99%
“…While this manuscript was under preparation, Rogg et al . published a paper on Coro2b in human and mouse podocytes 9 . They performed detailed studies in cultured podocytes, and showed that constitutive KO mice have normal glomerular structure and function but are partially protected from doxorubicin-induced glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that coronin-1A can directly interact with the ARP2/3 complex [86], is present at the leading edge during chemotaxis [78, 87], and plays a role in phagocytosis [87] and signal transduction [88]. Class II includes coronin-4 and coronin-5 (also called 2A and 2B), involved in focal adhesion turnover, reorganization of the cytoskeleton, and cell migration [89, 90]. The class III coronin-7 has an unusual structure and plays a role in Golgi morphology maintenance [91, 92].…”
Section: Pids Caused By Defective Cytoskeletal Regulationmentioning
confidence: 99%